Effect of ambient temperature on metabolic indices of fatigue during prolonged exercise - Febbraio, M. A.; Parkin, J. M.; Baldwin, J.; Zhao, S.; Carey, M. F. (Medicine & Science in Sports & Exercise, 1996)
It was found that fatigue in prolonged exercise in hot conditions is not related to carbohydrate (CHO) availability. Implication. To be safe, no matter what the climatic conditions, athletes should enter contests with carbohydrate levels as high as possible. When exercising in hot conditions, the degree of adaptation to heat and humidity will have a significant bearing on performance outcomes. Mechanisms other than CHO availability contribute to fatigue in hot conditions. This study investigated an aspect of the exaggerated hyperglycemia that occurs when exercising in the heat. This phenomenon is caused by an increase in liver glucose output, without any change in muscle glucose uptake. Total carbohydrate (CHO) oxidation is higher in high temperatures suggesting that muscle glycogenolysis is increased during exercise in the heat. Implication. CHO utilization is increased when exercising in the heat. Pre-contest and intra-contest CHO supplementation should be strictly monitored and slightly exaggerated above normal temperature ingestion quantities and frequencies.